Endodontic Treatment of a Mandibular Second Premolar with Type IV Wiene’s Root Canal: A Case Report - Noushad Matavan Chalil; Shravan Kini; Sunil Jose; Arun Narayanan; Shahnas Salahudeen; Faizal C. Peedikayil (Case Reports in Dentistry)
This case report describes an endodontic treatment of a mandibular second premolar with type IV root canal. A 26-year-old male patient reported pain in right mandibular second premolar. Clinical examination showed a large carious lesion with pulp exposure. Radiographs showed minimal periapical changes and slight widening of periodontal ligament space. Mandibular second premolars usually have one canal. The mandibular second premolar may present large number of anatomic variations. The clinician should be aware of the configuration of the pulp system. This case presents the diagnosis and clinical management of a mandibular second premolar with two distinct canals in the apical third of root (Type IV Wiene’s canal configuration), drawing particular attention to tactile examination of all the canal walls and obturating it with calamus 3D obturation system.